2013
DOI: 10.3389/fimmu.2013.00440
|View full text |Cite
|
Sign up to set email alerts
|

An Update on PYRIN Domain-Containing Pattern Recognition Receptors: From Immunity to Pathology

Abstract: Cytosolic pattern recognition receptors (PRRs) sense a wide range of endogenous danger-associated molecular patterns as well as exogenous pathogen-associated molecular patterns. In particular, Nod-like receptors containing a pyrin domain (PYD), called NLRPs, and AIM2-like receptors (ALRs) have been shown to play a critical role in host defense by facilitating clearance of pathogens and maintaining a healthy gut microflora. NLRPs and ALRs both encode a PYD, which is crucial for relaying signals that result in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 229 publications
(366 reference statements)
1
85
0
Order By: Relevance
“…ROS generation is frequently accompanied by K + efflux (Kowaltowski et al, 2009), although the mechanism for this remains unclear. The involvement of mitochondria in NLRP3 activation remains controversial (Ratsimandresy et al, 2013) despite several examples for DAMP-induced NLRP3 inflammasome activation (Tschopp and Schroder, 2010). Activation of the NLRP3 inflammasome by asbestos and silica has been associated with the production of ROS.…”
Section: Damps Identified By the Nlrp3 Inflammasomementioning
confidence: 98%
See 1 more Smart Citation
“…ROS generation is frequently accompanied by K + efflux (Kowaltowski et al, 2009), although the mechanism for this remains unclear. The involvement of mitochondria in NLRP3 activation remains controversial (Ratsimandresy et al, 2013) despite several examples for DAMP-induced NLRP3 inflammasome activation (Tschopp and Schroder, 2010). Activation of the NLRP3 inflammasome by asbestos and silica has been associated with the production of ROS.…”
Section: Damps Identified By the Nlrp3 Inflammasomementioning
confidence: 98%
“…Ion fluxes also play a role in NLRP3 inflammasome activation, such as K + efflux via ATP activation of its receptor P2X7 and calcium influx via multiple receptors. Mitochondrial-generated ROS also has been suggested to influence NLRP3 activation (Ratsimandresy et al, 2013). The mitochondria have been associated with the creation of ROS as a byproduct of stressors such as hypoxia, acidosis and membrane damage (Rajamäki et al, 2013).…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
“…Inflammasomes was thought to have a unique ability to integrate a myriad of signals from pathogen- and damage-associated molecular patterns into a proinflammatory response [36]. As the most extensively investigated of the inflammasomes identified, activation of the NLRP3 inflammasome can be achieved by a wide range of structurally dissimilar agonists, including pathogens, pore-forming toxins, environmental irritants, and endogenous damage-associated molecular patterns [37]. Our study found that NLRP3 activation is involved in the pathogenesis of LPS-induced PRTC cells' apoptosis and CLP-induced sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the AIM2-like receptor (ALR inflammasome) and DDX41 [DEAD/H helicase (DDX) protein] act as cytosolic DNA sensors [95,113]. ALR is a pyrin domaincontaining PRR that forms an inflammasome protein complex with an ASC adaptor to recognize viral and bacterial DNAs [113].…”
Section: Other Current Topics On Cytosolic Dna Sensors (Cdss)mentioning
confidence: 99%
“…ALR is a pyrin domaincontaining PRR that forms an inflammasome protein complex with an ASC adaptor to recognize viral and bacterial DNAs [113]. However, no counterparts of the AIM2 gene have been found in any fish species.…”
Section: Other Current Topics On Cytosolic Dna Sensors (Cdss)mentioning
confidence: 99%